Genome-wide association meta-analysis identifies five loci associated with postpartum hemorrhage - Westergaard, D; Steinthorsdottir, V; Stefansdottir, L; Rohde, PD; Wu, X; Geller, F; Tyrmi, J; Havulinna, AS; Solé-Navais, P; Flatley, C; Ostrowski, SR; Pedersen, OB; et al. (Nature Research, 2024)
Bleeding in early pregnancy and postpartum hemorrhage (PPH) bear substantial risks, with the former closely associated with pregnancy loss and the latter being the foremost cause of maternal death, underscoring the severe impact on maternal–fetal health. We identified five genetic loci linked to PPH in a meta-analysis. Functional annotation analysis indicated candidate genes HAND2, TBX3 and RAP2C/FRMD7 at three loci and showed that at each locus, associated variants were located within binding sites for progesterone receptors. There were strong genetic correlations with birth weight, gestational duration and uterine fibroids. Bleeding in early pregnancy yielded no genome-wide association signals but showed strong genetic correlation with various human traits, suggesting a potentially complex, polygenic etiology. Our results suggest that PPH is related to progesterone signaling dysregulation, whereas early bleeding is a complex trait associated with underlying health and possibly socioeconomic status and may include genetic factors that have not yet been identified.